Degree of availability writing expression skills among fourth- grade students (Field study in Hama city schools) (Journal of Hama University, 2026)
The aim of this research was to identify the appropriate creative writing skills for fourth-grade students and to assess the extent to which these skills are present in their written compositions. To achieve the objectives of the study, a list of essential writing skills for fourth-grade students was developed, along with a test designed to measure the availability of these skills among students, based on the previously prepared list.The research was conducted on a sample of 30 fourth-grade students during the first semester of the 2024–2025 academic year, using the descriptive-analytical method.The results indicated that some skills were present at an acceptable level based on students' responses (research sample), while other skills were found to be below the expected level. Additionally, certain skills were identified as needing further reinforcement. The study recommended revisiting the distribution and enhancement of writing skills, providing support for those not adequately developed, and conducting training sessions for teachers of the first educational cycle on effective methods for teaching written expression.
Keywords: Creative Writing Skills, Fourth Grade